Characterization of Rare Earth Elements in Tailing of Ex-Tin Mining Sands from Singkep Island, Indonesia - Yanuar Hamzah; Muhammad Mardhiansyah; Liong Nyuk Firdaus (Aceh International Journal of Science and Technology, 2018)
The objective of this research is to determine the rare earth elements (REEs) from themonazite minerals content of several tin tailing sands (TTS)of ex-tin mining area in Kuala Raya Singkep Island, Indonesia. We used the energy dispersive analysis of  X-ray (EDAX)-scanning electron microscopy (SEM) and x-ray diffraction (XRD) to characterize the contents of the samples. The coupled analytical of XRD with SEM/EDX approach enabled to be used for mineralogical identification on the heavy mineral as a rapid determination approach. The analysis of the samples indicates only the presence of REEs including lanthanum (La), cerium (Ce), and thorium (Th) are consistent with the identification of monazite and minerals in the tailing sand. The results show that the average REEs consist of La at 0.2 .%, Ce at 7.8 %, and Th at 2.0% respectively. It is concluded that monazite minerals in TTS has an economic potential to be developed. These monazite minerals can be used as material for semiconductor devices.